2D graphene/FeOCl heterojunctions with enhanced tribology performance as a lubricant additive for liquid paraffin. Issue 5 (20th January 2022) - Xie, Mengxin; Pan, Bingli; Li, Ning; Zhao, Shuang; Yan, Junjiang; Guo, Shihao; Chen, Zhe; Wang, Honggang
Abstract : Graphene/FeOCl (G/FeOCl) heterojunctions were prepared by microwave-pyrolysis, thoroughly characterised and used to probe the synergistic lubrication of G with FeOCl in liquid paraffin. We provide a pathway for low-friction lubricants by deploying G/FeOCl 2D materials. Abstract : The purpose of this study is to prepare graphene/FeOCl (G/FeOCl) heterojunctions via a microwave-pyrolysis approach and probe into the synergistic lubrication of G with FeOCl in liquid paraffin (LP). The morphology and chemical composition of specimens were analysed by utilizing scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and X-ray photoelectron spectroscopy (XPS) techniques. The tribological property of G/FeOCl was determined, and the interaction between the G/FeOCl heterojunction and friction pair was carried out through simulation calculations. The results indicated that neither G nor FeOCl significantly improved the lubrication performance of LP. However, together with FeOCl, G as lubrication additives greatly improved the lubrication performance of LP. Under the load of 1.648 GPa, the mean friction coefficient and wear scar diameter of LP containing 0.20 wt% G/FeOCl were 66.1% and 44.7% inferior to those of pure LP, respectively. Scanning electron microscopy (SEM) and elemental mapping analyses of worn scars revealed the formation of G/FeOCl layer tribofilms that prevent direct contact between metals. In addition, the high interfacial energy between graphene and FeOCl calculated based on first-principles density functional theory (DFT) further confirmed that graphene and FeOCl simultaneously form friction films with wear resistance and wear reduction effect at the friction interface, which is consistent with the experimental results. This study, therefore, provides a pathway for low-friction lubricants by deploying G/FeOCl two-dimensional material systems.